Specific characteristics of physical examination made by the nurse - Laganá, Maria Teresa Cícero; Friedlander, Maria Romana; Pimenta, Cibele Andrucioli M.; Silva, Maria Júlia P. da; Imanich, Rose Meire (Revista da Escola de Enfermagem da USP, 1993)
The purpose of this work is focused on the physical examinations made by the nurse, identifying four basic assumption originated from the performance of this procedure. It also suggests indicative guidelines of specificity to the nursing physical examinations.